2006
DOI: 10.1088/0031-9155/51/23/n01
|View full text |Cite
|
Sign up to set email alerts
|

Dose area product evaluations with Gafchromic®XR-R films and a flat-bed scanner

Abstract: Gafchromic XR-R films are a useful tool to evaluate entrance skin dose in interventional radiology. Another dosimetric quantity of interest in diagnostic and interventional radiology is the dose area product (DAP). In this study, a method to evaluate DAP using Gafchromic XR-R films and a flat-bed scanner was developed and tested. Film samples were exposed to an x-ray beam of 80 kVp over a dose range of 0-10 Gy. DAP measurements with films were obtained from the digitalization of a film sample positioned over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…19 As per ISP recommendations, as well as the successful results of other researchers, the calibration films were scanned with an Epson Expression 10000XL flatbed document scanner 24Ϯ 4 h postexposure. 19,[21][22][23][24][25]33,36 The postexposure time dependence of film darkening was also evaluated. The software package "EPSON SCAN" ͑Version 3.04A͒ was used to control the scan parameters, which included scanning in "Professional Mode," reflective mode, with all imaging adjustment options turned off, and with a resolution of 72 dpi.…”
Section: Iid Measurement Of the Film Reflective Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…19 As per ISP recommendations, as well as the successful results of other researchers, the calibration films were scanned with an Epson Expression 10000XL flatbed document scanner 24Ϯ 4 h postexposure. 19,[21][22][23][24][25]33,36 The postexposure time dependence of film darkening was also evaluated. The software package "EPSON SCAN" ͑Version 3.04A͒ was used to control the scan parameters, which included scanning in "Professional Mode," reflective mode, with all imaging adjustment options turned off, and with a resolution of 72 dpi.…”
Section: Iid Measurement Of the Film Reflective Densitymentioning
confidence: 99%
“…19 Film calibration and film-property measurements have been performed for several versions of fluoroscopic energy-range radiochromic film ͑e.g., GafChromic ® MD-55, XR-R, and XR-RV2 films͒. [19][20][21][22][23][24][25] This work examines the response of a newly formulated radiochromic film ͑GafChromic ® XR-RV3͒ to four National Institute of Standards and Technology ͑NIST͒ traceable, moderately filtered x-ray beams in the energy range of 60-120 kVp, similar to beam qualities used for interventional procedures. The calibration of a commercial flatbed scanner for the digitization of radiochromic films is also reported.…”
Section: Introductionmentioning
confidence: 99%
“…Among the multiple fit functions tested in this study, exponential equations 17,19 were found to be inappropriate for XR-RV3 film calibrations. Errors on the high dose values generally exceeding 40% were obtained with these functions since the film response with dose does not show exponential behavior (cf.…”
Section: C1 Fitting Equation and Algorithmmentioning
confidence: 89%
“…The CT dose phantom has been designed to measure the CT dose index (CTDI) 16,17 , the CDTI variations (CTDIw and CTDIvol), and the dose-length product (DLP) 17 using a pencil-type ionization chamber. There are two types of CT dose phantoms, a body phantom (32 cm) and a head phantom (16 cm) 16,18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…There are two types of CT dose phantoms, a body phantom (32 cm) and a head phantom (16 cm) 16,18,19 . Each phantom has five probe holes with inside diameter 1.31 cm to insert a penciltype ionization chamber.…”
Section: Introductionmentioning
confidence: 99%